Rural migrants and their marital problems: discourses of governing and knowledge production in China. Issue 1 (2nd January 2019) - Sun, Wanning
ABSTRACT: Since 2010, there has been a noticeable increase in China's academic publications about young rural migrants' love life. Social scientists play a crucial role in shaping public opinions and policy formations regarding the welfare of individuals from this disadvantaged group. Knowledge about rural migrants' marital problem – the nature of their problem, its causes and possible solutions – provides legitimation to the government's social policies, and for this reason it warrants careful investigation. Taking an interpretative policy analysis approach, the article analyses the recurring narrative and discursive frameworks in the Chinese-language scholarship. Furthermore, it juxtaposes scholarship produced inside and outside China in order to bring into sharp relief the 'Chinese characteristics' of China's scholarly publications in the fields of social sciences. The article also discusses why the private life of rural migrants has become a source of political and social anxiety. This discussion demonstrates the complex connection between socioeconomic inequality, social policy formations, and the cultural politics of class in post-socialist China.